Preparation of Ag2O modified silica abrasives and their chemical mechanical polishing performances on sapphire - Baichun Zhang; Hong Lei; Yi Chen (Friction)
Abstract The chemical mechanical polishing (CMP) process has become a widely accepted global planarization technology. The abrasive material is one of the key elements in CMP. In the presented paper, an Ag-doped colloidal SiO2 abrasive is synthesized by a seed-induced growth method. It is characterized by time-of-flight secondary ion mass spectroscopy and scanning electron microscopy to analyze the composition and morphology. The CMP performance of the Ag-doped colloidal silica abrasives on sapphire substrates is investigated. Experiment results show the material removal rate (MRR) of Ag-doped colloidal silica abrasives is obviously higher than that of pure colloidal silica abrasives under the same testing conditions. The surfaces that are polished by composite colloidal abrasives exhibit lower surface roughness (Ra) than those polished by pure colloidal silica abrasives. Furthermore, the acting mechanism of Ag-doped colloidal SiO2 composite abrasives in sapphire CMP is analyzed by X-ray photoelectron spectroscopy, and analytical results show that element Ag forms Ag2O which acts as a catalyst to promote the chemical effect in CMP and leads to the increasing of MRR.